Analisis Meta tentang Penggunaan Material dan Teknologi Ramah Lingkungan dalam Industri Pembungkusan Makanan - Rifansyah, Muhammad Rio; Zaydan, Sadid (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The food packaging industry faces significant challenges in balancing food protection performance with increasing environmental sustainability demands, driven by the rapid growth of plastic waste and global food loss. This study aims to identify, compare, and assess sustainable food packaging materials and technologies to support the transition toward environmentally responsible packaging systems. A meta-analysis of more than 200 peer-reviewed publications from 2018–2025 was conducted, integrating a systematic literature review with Life Cycle Assessment (LCA) based on ISO 14040/14044 standards. The analysis covered polysaccharide- and protein-based biopolymers, Polylactic Acid (PLA), Polyhydroxyalkanoates (PHA), as well as nanocomposites and smart packaging technologies.